2005
DOI: 10.1111/j.1365-2958.2005.04944.x
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐ribosylation of dinitrogenase reductase in Azospirillum brasilense is regulated by AmtB‐dependent membrane sequestration of DraG

Abstract: SummaryNitrogen fixation in some diazotrophic bacteria is regulated by mono-ADP-ribosylation of dinitrogenase reductase (NifH) that occurs in response to addition of ammonium to the extracellular medium. This process is mediated by dinitrogenase reductase ADPribosyltransferase (DraT) and reversed by dinitrogenase reductase glycohydrolase (DraG), but the means by which the activities of these enzymes are regulated are unknown. We have investigated the role of the P II proteins (GlnB and GlnZ), the ammonia chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
99
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(107 citation statements)
references
References 45 publications
(56 reference statements)
8
99
0
Order By: Relevance
“…The model is supported by copurification experiments and gel filtration with purified components that demonstrate the protein-protein interactions and in vitro nitrogenase assays with purified components. The mechanism is relatively simple and contrasts with the more complex regulation found in some Proteobacteria involving ADP-ribosylation of nitrogenase reductase by DraT and DraG (3), binding and membrane sequestration of DraG to the ammonia transporter AmtB by PII proteins, and covalent modification of the PII proteins by the glutamine sensor GlnD (12). The wide phylogenetic distribution of nifI 1 and nifI 2 genes, and their almost exclusive linkage to nifHDK genes, suggests that this mode of regulation may be conserved in a variety of diazotrophic Archaea and Bacteria (30).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The model is supported by copurification experiments and gel filtration with purified components that demonstrate the protein-protein interactions and in vitro nitrogenase assays with purified components. The mechanism is relatively simple and contrasts with the more complex regulation found in some Proteobacteria involving ADP-ribosylation of nitrogenase reductase by DraT and DraG (3), binding and membrane sequestration of DraG to the ammonia transporter AmtB by PII proteins, and covalent modification of the PII proteins by the glutamine sensor GlnD (12). The wide phylogenetic distribution of nifI 1 and nifI 2 genes, and their almost exclusive linkage to nifHDK genes, suggests that this mode of regulation may be conserved in a variety of diazotrophic Archaea and Bacteria (30).…”
Section: Discussionmentioning
confidence: 88%
“…8 and 9), including ADP-ribosylation of NifH (10)(11)(12). The best studied examples, GlnB and GlnK of Escherichia coli and other Proteobacteria, are homotrimers (13).…”
mentioning
confidence: 99%
“…We therefore have suggested that AmtB activity might be regulated by GlnK (16). Indeed, in vivo, GlnK binds rapidly and reversibly to AmtB in response to an extracellular ammonium shock (Ն50 M extracellular ammonium) (17), and this interaction has also been shown in a number of other eubacterial species (16,(18)(19)(20). Methylammonium uptake by AmtB is also inhibited by a GlnK variant that forms an irreversible complex, supporting the concept that GlnK regulates ammonium flux through AmtB (17).…”
mentioning
confidence: 72%
“…The structure emphasizes that the primary function of GlnK is almost certainly regulation of ammonium flux into the cell, and the almost ubiquitous linkage of the glnK and amtB genes suggests that regulation of the ammonia channel may be the ancestral role of P II proteins (38). However, in some systems, complex formation might also serve other functions such as sequestration of cytoplasmic proteins involved in regulation of nitrogen metabolism as suggested by recent studies in Azospirillum brasilense (19) and Bacillus subtilis (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation